Elevated septal native T1 time in cardiac magnetic resonance imaging suggesting myocardial fibrosis in young kidney transplant recipients - Tim Alexander Ubenauf; Jeannine von der Born; Rizky I. Sugianto; Carl Grabitz; Elena Lehmann; Nima Memaran; Nele Kanzelmeyer; Jan Falk; Nigar Babazade; Samir Sarikouch; Diane Miriam Renz; Bernhard Magnus Wilhelm Schmidt; et al. (Journal of Cardiovascular Magnetic Resonance)
ABSTRACT: Background: Patients after kidney transplantation (KTx) in childhood show a high prevalence of cardiac complications, but the underlying mechanism is still poorly understood. In adults, myocardial fibrosis detected in cardiovascular magnetic resonance (CMR) imaging is already an established risk factor. Data for children after KTx are not available. This study aimed to explore cardiac function and structure with focus on myocardial fibrosis and associated risk factors in KTx recipients. Methods: Forty-six KTx recipients (mean age 16.0 ± 3.5 years) and 46 age- and sex-matched healthy controls were examined with non-contrast CMR imaging. Native T1 time (nT1), a marker for myocardial fibrosis, was measured at the interventricular septum. Other parameters comprised left ventricular mass index (LVMI), left ventricular ejection fraction (LVEF), and global longitudinal strain (GLS). Multivariable linear regression analyses were used to explore associations with nT1. Results: Mean nT1 was significantly higher in KTx recipients compared to controls (1198.1 ± 48.8 vs 1154.4 ± 23.4 ms, p < 0.0001). 46% (21/46) had a nT1 above the upper limit of the normal range (mean + 2 standard deviations of controls). KTx recipients showed higher LVMI z-scores (0.1 ± 1.1 vs −0.3 ± 0.7, p = 0.026), higher LVEF (67.3 ± 3.8% vs 65.3 ± 3.6%, p = 0.012), and lower GLS (−19.0 ± 2.1% vs −20.3 ± 2.7%, p = 0.010). Higher systolic blood pressure (ß = 1.284, p = 0.001), LVMI (ß = 1.542, p < 0.001), and LVEF (ß = 3.535, p = 0.026) were associated with longer nT1 only in KTx recipients, but not in controls. Only 2 KTx recipients exhibited left ventricular hypertrophy; however, a total of 18 displayed elevated nT1 with LVMI z-score within the normal range. Conclusion: Our data suggest the presence of cardiac remodeling with myocardial fibrosis in a significant proportion of young KTx recipients. Non-contrast CMR imaging has the potential to visualize early structural cardiac changes and could become an important diagnostic adjunct in the follow-up of KTx recipients. Longitudinal studies are needed to further evaluate the importance of nT1 in early identification of those at high risk for sudden cardiac death allowing to integrate preventive strategies.